QbD-based design and characterization of mucoadhesive microspheres of quetiapine fumarate with improved oral bioavailability and brain biodistribution potential - Someshwar Komati; Suryakanta Swain; Muddana Eswara Bhanoji Rao; Bikash Ranjan Jena; Sambamoorthy Unnam; Vishali Dasi (Faculty of Pharmacy, Cairo University, 2018)
The present work aims to discuss on Quality by Design based development and characterization of the sustained release mucoadhesive microspheres of quetiapine fumarate. The microspheres were prepared by non-aqueous solvent evaporation process. Factor screening study was carried out using fractional factorial design for identifying the influential factors. Systematic optimization of microspheres was accomplished by Box-Behnken design and characterized for particle size, entrapment efficiency, in vitro drug release and ex vivo mucoadhesion strength, which indicated that microspheres were consequence to be spherical and free flowing in nature. The microspheres exhibited high drug entrapment efficiency and in vitro drug release in a sustained manner, which was considered to be dependent on the concentration of rate controlling polymers. Ex vivo wash-off test on microspheres indicated good mucoadhesive property on excised goat intestinal mucosa. Out of all the accepted formulation, F6 was preferred as the optimized formulation. In vivo pharmacokinetic and brain biodistribution study revealed significant increase in the levels of drug in blood plasma and brain homogenates from the optimized formulation vis-à-vis the pure drug suspension. Overall, current study corroborated significant improvement in the biopharmaceutical attributes of quetiapine fumarate from mucoadhesive microspheres, which can be effectively used for management of depression and schizophrenia. Keywords: Quality by Design, DoE, Sustained release, Mucoadhesion, Depression